2019
DOI: 10.13075/ijomeh.1896.01333
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress in the Italian banking population and its association with recovery experience

Abstract: Objectives: Over the past decade, there has been a markedly growing interest in issues involving work-related stress in Europe. In Italy, according to Eurofound, research has demonstrated high levels of stress in the banking sector. With this in mind, a study was conducted to evaluate the peculiarities of hindrance and challenge stressors, and their links with recovery in the Italian banking population. Material and Methods: The health and safety managers of a major Italian banking group were contacted and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…For example, Kan and Yu (2016) studied depression among bank employees and found that extrinsic effort, overcommitment, and work-family conflict had positive effects on depressive symptoms. Because workrelated stress is common in the banking sector, future studies will do well to pay attention to whether it influences the relationship between voice and employee performance (Giorgi et al, 2019).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…For example, Kan and Yu (2016) studied depression among bank employees and found that extrinsic effort, overcommitment, and work-family conflict had positive effects on depressive symptoms. Because workrelated stress is common in the banking sector, future studies will do well to pay attention to whether it influences the relationship between voice and employee performance (Giorgi et al, 2019).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Therefore, bank employees; are a vulnerable group at a high-level of risk for occupational stress. Research has recommended that banks adopt corporate policies that include stress prevention activities, with the more general goal of improving workers' mental health (20). Previous studies have pointed out that the risk factor for job burnout increases with occupational stress; occupational stress affects entire proportions of job burnout directly and indirectly (21).…”
Section: Introductionmentioning
confidence: 99%
“…Not all teachers are equally vulnerable to developing burnout, because the subjective efficacy and ability to make decisions represents protective factors for the manifestation of the syndrome [14]. It is worth considering a further aspect concerning the aging trend of school staff in Italy [15].…”
Section: Introductionmentioning
confidence: 99%